Kiran clinic: Community owned primary health care - A case study from rural Wardha - V A Bhagat; A V Raut; S S Gupta; A M Mehandale; B S Garg (Wolters Kluwer Medknow Publications, 2017)
Background: Primary health care is the right of each and every human being. One of the innovations in making primary health care available to the community is the community owned primary health care clinics (Kiran clinics) functional in the villages of field practice area of Department of Community Medicine at Mahatma Gandhi Institute of Medical Sciences (MGIMS), Sewagram. This case study aimed to document the process of formation and evolution of one of such Kiran clinic (KC) with a focus on identifying the facilitating factors for evolution and sustainability of the KC. Material and methods: In this qualitative study, In depth interview (IDI), observations of Kiran clinic day and meetings of management committee meetings were undertaken. All the IDI were tape recorded, transcript prepared and analysis was done manually. Results: Facilitating factors for evolution and sustainability of Kiran clinic in Salod village were voluntary participation, community dialogue, capacity building of committee members, knowledge and ownership of committee members, transparency in work/quality monitoring, and quality services responsive to health need. Conclusions: Kiran clinic is a socially acceptable, feasible and a sustainable model for provision of required health services to villagers.